Medicinal Plants: A Potential Source of Compounds for Targeting Cell Division - Ihsan N. Zulkipli; Sheba R. David; Rajan Rajabalaya; Adi Idris (AboutScience Srl, 2015)
Modern medicinal plant drug discovery has provided pharmacologically active compounds targeted against a multitude of conditions and diseases, such as infection, inflammation, and cancer. To date, natural products from medicinal plants remain a solid niche as a source from which cancer therapies can be derived. Among other properties, one favorable characteristic of an anticancer drug is its ability to block the uncontrollable process of cell division, as cancer cells are notorious for their abnormal cell division. There are numerous other documented works on the potential anticancer activity of drugs derived from medicinal plants, and their effects on cell division are an attractive and growing therapeutic target. Despite this, there remains a vast number of unidentified natural products that are potentially promising sources for medical applications. This mini review aims to revise the current knowledge of the effects of natural plant products on cell division.